2019
DOI: 10.2135/cropsci2019.02.0136
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Gain Over 30 Years of Spring Wheat Breeding in Brazil

Abstract: Wheat (Triticum aestivum L.) is one of the most important crops in the world. Brazil is one of the largest importers of this cereal, and wheat breeding programs are attempting to increase productivity and reduce external dependence. The objectives of this study were to quantify the spring wheat genetic gain in Brazil between 1984 and 2014 using data from multienvironment trials, and to verify if the genetic gain stagnated after the 2000s. This study used a highly unbalanced dataset containing grain yield (GY) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
3
15
0
3
Order By: Relevance
“…Beche et al (2014) evaluated wheat cultivars released in Brazil between 1940 and 2009 and observed a genetic gain of 29 kg ha -1 year -1 (0.92% year -1 ). Similar results were presented by Bornhofen et al (2018) and Woyann et al (2019), indicating a significant genetic gain for this crop in Brazil. However, to meet food demand by 2050, the annual increase in food production needs to be on the order of 2.4% (Ray et al 2013).…”
Section: Introductionsupporting
confidence: 86%
“…Beche et al (2014) evaluated wheat cultivars released in Brazil between 1940 and 2009 and observed a genetic gain of 29 kg ha -1 year -1 (0.92% year -1 ). Similar results were presented by Bornhofen et al (2018) and Woyann et al (2019), indicating a significant genetic gain for this crop in Brazil. However, to meet food demand by 2050, the annual increase in food production needs to be on the order of 2.4% (Ray et al 2013).…”
Section: Introductionsupporting
confidence: 86%
“…The estimated annual genetic gains in GY for spring wheat in Norway since 1972 (on average 17.8 kg ha −1 , 0.34%) show similarity to gains determined in numerous collections worldwide (Ahrends et al, 2018;Crespo-Herrera et al, 2017;Dube et al, 2019;Evans et al, 1980;Oury et al, 2012;Rodrigues et al, 2007;Voss-Fels et al, 2019;Woyann et al, 2019), although they are slightly lower. The gains being relatively small show that GY was not the only priority for breeders.…”
Section: Grain Yieldsupporting
confidence: 69%
“…The author also points to the increased photosynthetic capacity and loading resistance as key traits for average grain yield increase. Improved grain yield potential may also be related to changes in growth and developmental phases (Woyann et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Brazilian wheat germplasm still has a satisfactory level of variability (Sherlosky et al., 2018), which leads us to infer that Brazil is far from reaching genetic stagnation in wheat production. Genetic stagnation has been described in regions where wheat presents high production means (Woyann et al., 2019), mainly due to the narrowing of genetic bases (Brisson et al., 2010).…”
Section: Discussionmentioning
confidence: 99%